Implementasi Data Mining Estimasi Ketersediaan Lahan Pembuangan Sampah menggunakan Algoritma Simple Linear Regression - Robi Yanto (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
The high consumption activity done by the community is directly proportional to the increase of waste production. One of the problems of high waste production is the low public awareness of waste management. This is a problem encountered in big cities. Garbage has a negative impact on changes in existing natural conditions, namely the occurrence of air pollution, water and soil that causes the environment to become unhealthy. Waste management activities through the socialization of the 3R (Reduce, Reuse, Recycle) program on waste, but this program has not maximized the public awareness about the importance of a healthy environment. as population increases have an impact on increasing waste production. So that requires sufficient land disposal land in the long term. To overcome these problems, data analysis of long-term waste land disposal estimation using data mining techniques is used. from the data mining analysis using a simple linear regression algorithm with respect to population growth from 2018 until 2025 by 201484 people, it is known that the increase of waste from 2018 to 2025 is 36,052,326 tons. So from the land area of ​​30000 M2 only available land disposal until the year 2025 of 5,965.1 M2.